Policies that affect the competitiveness of sawn wood production in Mexico - Fuentes-López, Martha E.; García-Salazar, J. Alberto; Zamudio-Sánchez, Francisco J.; Matus-Gardea, J. Arturo (Instituto de Ecología, A.C., 2016)
Mexican sawn wood is facing a lack of competitiveness with respect to imported wood. Over the period 1993-1995 average national production was able to supply 80% of the national consumption whereas by the period 2001-2003 only was capable of supplying 24%. In order to determine the factors that could revert this tendency, a non linear programming model was used. Results indicate that if there were subsidies a 30% reduction in production costs would decrease imported wood in about 1 ,1%, which means 50,139 m3 of sawn wood, and it would increase the national production in 2,1%. A 20 % reduction in transportation cost would lead to a rise in the national sawn wood production of 3,8%, this is 90 500 m3 in terms of sawn wood; consequently, imported sawn wood would decrease in 2 ,2%, which means 102 034 m3 of sawn wood. If a 6% tariff above the international price were to be implemented, the national production would increase in about 5,6%, this means 132 355 m3 of sawn wood. This tariff will help to decrease imported wood in about 9,5%, this is 306 923 m3 of sawn wood with respect to those of the 2001-2003 period.